The MqsR/MqsA toxin/antitoxin system protects Escherichia coli during bile acid stress. (14th February 2015) - Kwan, Brian W.; Lord, Dana M.; Peti, Wolfgang; Page, Rebecca; Benedik, Michael J.; Wood, Thomas K.
Summary Toxin/antitoxin (TA) systems are ubiquitous within bacterial genomes, and the mechanisms of many TA systems are well characterized. As such, several roles for TA systems have been proposed, such as phage inhibition, gene regulation and persister cell formation. However, the significance of these roles is nebulous due to the subtle influence from individual TA systems. For example, a single TA system has only a minor contribution to persister cell formation. Hence, there is a lack of defining physiological roles for individual TA systems. In this study, phenotype assays were used to determine that the MqsR/MqsA type II TA system of Escherichia coli is important for cell growth and tolerance during stress from the bile salt deoxycholate. Using transcriptomics and purified MqsR, we determined that endoribonuclease toxin MqsR degrades YgiS mRNA, which encodes a periplasmic protein that promotes deoxycholate uptake and reduces tolerance to deoxycholate exposure. The importance of reducing YgiS mRNA by MqsR is evidenced by improved growth, reduced cell death and reduced membrane damage when cells without ygiS are stressed with deoxycholate. Therefore, we propose that MqsR/MqsA is physiologically important for E. coli to thrive in the gallbladder and upper intestinal tract, where high bile concentrations are prominent.